Formulation and evaluation of piperacillin tazobactam loaded aquasomal gel for the treatment of noma - Sandeep S K; Anasuya Patil; Shafura S; Deepa Bagur Paramesh; Mahanthesh H M (Journal of Applied Pharmaceutical Research, 2026)
Background: Noma is a rapidly progressing gangrenous disease that affects the oral and facial tissues, mainly in malnourished and immunocompromised children. Delayed intervention often results in severe tissue destruction, facial deformity, and high morbidity. Although broad-spectrum antibiotics are routinely employed, conventional dosage forms often fail to achieve sufficient drug concentrations at the site of infection. Poor local absorption, limited tissue penetration, and the need for repeated administration reduce therapeutic effectiveness and patient compliance. Hence, a novel topical drug delivery system is required to enhance local drug delivery and clinical outcomes. This manuscript aims to formulate and evaluate a Piperacillin–Tazobactam-loaded Aquasomal gel for topical treatment of Noma. Methodology: Aquasomes composed of a calcium phosphate core coated with trehalose were prepared by the sonication method for topical delivery of Piperacillin–Tazobactam. A Central Composite Design (CCD) using Design-Expert® software was used to optimize formulation variables to improve entrapment efficiency and control drug release. The optimized Aquasomes were evaluated for particle size, polydispersity index, zeta potential, and drug entrapment efficiency, and then incorporated into a 1% Carbopol gel. Results & Discussion: The optimized formulation exhibited a particle size of 186 nm, a zeta potential of –19.37 mV, an entrapment efficiency of 68.18%, and sustained drug release of 61.1%. The gel exhibited suitable physicochemical properties and strong antibacterial activity against methicillin-resistant Staphylococcus aureus. Conclusion: The developed Aquasomal gel represents a promising topical therapy for the effective management of Noma.